Religion of a different color race and the Mormon struggle for whiteness - Reeve, W. Paul (Oxford University Press, 2015)
The Protestant white majority in the nineteenth century was convinced that Mormonism represented a racial - not merely religious - departure from the mainstream, and they spent considerable effort attempting to substantiate their claims. At least some of that effort came through persistent attacks on the collective Mormon body. Mormons responded with aspirations toward whiteness. It was a back-and-forth struggle between what outsiders imagined and what Mormons believed. Mormons ultimately emerged triumphant but not unscathed.